PENGARUH KETERSEDIAAN PRODUK DAN PENGALAMAN BERBELANJA TERHADAP PEMBELIAN ULANG PADA KONSUMEN TOKO BUKU ZANAFA PEKANBARU - Izarni, Nana; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research was conducted at Zanafa Panam Pekanbaru Bookstore. The purpose of this study was to determine the effect of product availability and shopping experience on repeat purchases of consumers at Zanafa Panam Pekanbaru Bookstore. Product Availability (X1) and Shopping Experience (X2) as independent variables while Repeat Purchase (Y) as dependent variable. The method used in this study is descriptive and quantitative statistics. The method used in this study is descriptive and quantitative statistics. The population in this study were consumers at the Zanafa Panam Pekanbaru Bookstore. The sample in this study was 96 respondents using the accidental sampling technique. The data used in this study were obtained through the process of distributing questionnaires that were tested statistically through the SPSS program. The results of this study obtained were that product availability had an effect on consumer repeat purchases, shopping experience had an effect on consumer repeat purchases, and product availability and shopping experience had an effect on consumer repeat purchases at the Zanafa Panam Pekanbaru Bookstore. Keywords: Product Availability, Shopping Experience, Repeat Purchase